Implementation of risk management framework in supply chain: A tale from a biofuel company in Indonesia - Rachmat Affriadi Anggara (The University of Manchester, Manchester Business School, 2011)
This paper examines the implementation of risk management within a supply chain. Using FMEA (Failure Mode and Effect Analysis) methodology as the risk management framework, this research investigates the overall supply chain network in the firm, identifies the inherent risks along its supply chain, assesses those risks, categorises those risks according to their level, and explores risk mitigation strategies. The study employs a qualitative approach and gathers first-hand data by means of semi-structured interviews to collect nuanced insights that underpin the FMEA method. Interviews with the firm's supply chain experts also reveal some critical risks along with their mitigation strategies. This study offers a practical implementation of FMEA in the supply chain, increases focal points on the most imminent risks, prioritises risk mitigation plans, and improves the sustainability of the firm's overall supply chain. Optimistically, in the end, this study seeks to enhances the sustainability in Indonesia's biofuel industry.
Keywords: 330; supply chain management; risk management; failure mode and effect analysis; biofuels; risk assessment; mitigation strategy; small-medium enterprise